Are the Politically Active Better Represented? - Lindqvist, Jesper; Oser, Jennifer; Dassonneville, Ruth; Persson, Mikael; Sundell, Anders (Political Behavior, 2026)
Political participation is considered an important path for people to influence politics. However, whether those who participate actually see more of their preferred policies implemented remains an open question. We address this question by analyzing cross-national data connecting opinions to subsequent policy implementation on multiple policy issues. Based on an analysis of data on more than 270,000 survey respondents in 40 countries from 1996 to 2016, we show that voters are at most only slightly, but not substantially better represented than nonvoters. In contrast to the negligible effect sizes for voting, citizens who are active in multiple types of nonelectoral political activity are better represented than those who are inactive. We subsequently examine whether the observed relationships can be explained by socio-economic status, as well as attitudinal engagement such as political trust and political efficacy. Our findings show that the cross-national positive association between nonelectoral participation and opinion-policy congruence remains even when controlling for these factors. Our concluding discussion highlights directions for future research that pinpoint the causal mechanisms that link nonelectoral participation with subsequent opinion-policy congruence.
Publisher Copyright: © The Author(s) 2026.
Keywords: Demonstrating; Nonelectoral participation; Opinion-policy congruence; Political participation; Representation; Voting